Narrativas docentes sobre os caminhos da educação quilombola na comunidade Pau d’Arco em Arapiraca, Alagoas - Santos, Lhara Letícia de Oliveira (2022)
The research has as general objective to understand the paths taken by a group of teachers from Escola Luiz Alberto de Melo in the construction of a teaching focused on quilombola education and positive ethnic-racial relations in the community of Pau d'Arco in Arapiraca, Alagoas. Therefore, we defined as specific objectives to identify the concepts and theoretical relationships between Law 10.639/2003; Education for Ethnic-Racial Relations and Quilombola School Education; Contextualize the personal and professional training processes of a group of teachers from Escola Luiz Alberto de Melo through their narratives; To describe the dynamics of the elaboration and execution of the Project Constructing an Afro-descendant Identity, in its 2015 edition, “Education of Ethnic-racial Relations” and to conceptualize the relationship between teaching history and the meanings of sankofa philosophy. As initial methodological paths, we list oral history, in its techniques of bibliographic and documentary research and interviews. In the latter case, taking into account the specificities that need attention for its execution due to the fact that we are living a period of the covid-19 pandemic that forces us to stay in social distancing and isolation. This methodology was taken into account during our research due to the density it presents and the contributions it can generate by allowing the fluid transit of information transmitted by our collaborators. As theoretical foundations we use some studies such as Rufino (2020; 2021), Ribeiro (2019), Gomes (2006), Munanga (2005) and Sodré (2012). We understand that in Pau d’Arco there was a crossroads of powerful teaching meetings so that education for Ethnic-racial relations and quilombola education gained format, direction and meaning. The ancestral force that exists within the community itself and expands beyond its borders.